Epigenomic modifications induced by hatchery rearing persist in germ line cells of adult salmon after their oceanic migration. (4th May 2021) - Leitwein, Maeva; Laporte, Martin; Le Luyer, Jeremy; Mohns, Kayla; Normandeau, Eric; Withler, Ruth; Bernatchez, Louis
Abstract: Human activities induce direct or indirect selection pressure on natural population and may ultimately affect population's integrity. While numerous conservation programs aimed to minimize human‐induced genomic variation, human‐induced environmental variation may generate epigenomic variation potentially affecting fitness through phenotypic modifications. Major questions remain pertaining to how much epigenomic variation arises from environmental heterogeneity, whether this variation can persist throughout life, and whether it can be transmitted across generations. We performed whole genome bisulfite sequencing (WGBS) on the sperm of genetically indistinguishable hatchery and wild‐born migrating adults of Coho salmon ( Oncorhynchus kisutch ) from two geographically distant rivers at different epigenome scales. Our results showed that coupling WGBS with fine‐scale analyses (local and chromosomal) allows the detection of parallel early‐life hatchery‐induced epimarks that differentiate wild from hatchery‐reared salmon. Four chromosomes and 183 differentially methylated regions (DMRs) displayed a significant signal of methylation differentiation between hatchery and wild‐born Coho salmon. Moreover, those early‐life epimarks persisted in germ line cells despite about 1.5 year spent in the ocean following release from hatchery, opening the possibility for transgenerational inheritance. Our results strengthen the hypothesis that epigenomic modifications environmentally induced during early‐life development persist in germ cells of adults until reproduction, which could potentially impact their fitness.